2015
DOI: 10.1111/bcpt.12530
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Voriconazole Trough Levels in Haematological Patients: Influence of Comedications with cytochrome P450(CYP) Inhibitors and/or with CYP Inhibitors plus CYP Inducers

Abstract: Voriconazole plasma exposure greatly varies among haematological patients. The purpose of this study was to identify the magnitude of influence of comedications with CYP inhibitors and/or with CYP inhibitors plus CYP inducers on voriconazole trough level (C min ). Voriconazole C min was retrospectively assessed among haematological patients who underwent therapeutic drug monitoring (TDM). Univariate and multivariate linear mixed-effect regression analyses were performed to identify the independent predictors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Three studies (Eiden et al, Dolton et al, Naito et al) 28,29,31 reported that glucocorticoids slightly elevated the metabolism of voriconazole, although it did not affect the plasma exposure of voriconazole. Two studies (Dolton et al, Cojutti et al) 27,34 found that co-administration of voriconazole with glucocorticoids led to a significant decrease in normalized voriconazole C min (P < 0Á001), and co-administration of methylprednisolone and dexamethasone had a greater effect on voriconazole concentration than did prednisone or prednisolone co-administration (Table 3).…”
Section: Effects Of Cyp450 Inducersmentioning
confidence: 98%
“…Three studies (Eiden et al, Dolton et al, Naito et al) 28,29,31 reported that glucocorticoids slightly elevated the metabolism of voriconazole, although it did not affect the plasma exposure of voriconazole. Two studies (Dolton et al, Cojutti et al) 27,34 found that co-administration of voriconazole with glucocorticoids led to a significant decrease in normalized voriconazole C min (P < 0Á001), and co-administration of methylprednisolone and dexamethasone had a greater effect on voriconazole concentration than did prednisone or prednisolone co-administration (Table 3).…”
Section: Effects Of Cyp450 Inducersmentioning
confidence: 98%
“…An in vitro study has identified glucocorticoid receptor binding sites in the promoter region of the CYP2C19 gene and demonstrated up‐regulation of CYP2C19, supporting an inductive effect of glucocorticoids on CYP2C19 . There are limited data regarding the interaction between voriconazole and corticosteroids in clinical practice . Dolton et al found that concomitant dexamethasone use was associated with a 3.75‐fold decrease in voriconazole concentrations .…”
Section: Dips Algorithm (Drug Interaction Probability Scale); the Intmentioning
confidence: 99%
“…There is a large body of evidence demonstrating that therapeutic success with voriconazole is contingent on achieving a therapeutic trough plasma concentration at steady state [79], and response rates approach 100% when trough concentrations of at least 2 mg/L are attained early in the course of therapy [3,10,11]. However, the recommended weight-based voriconazole dosing for the treatment IFIs, which consists of a loading dose of 6 mg/kg every 12 hours for the first 24 hours followed by a maintenance dose of 4 mg/kg every 12 hours, is associated with a wide inter-individual variability in voriconazole exposure [7,12], with reported troughs ranging from 0.2 mg/L to 13.5 mg/L [12,13]. …”
Section: Introductionmentioning
confidence: 99%